Brexit: An Exploratory Analysis of the Macroeconomic Effects on the British Economy - Bento, João Alves (2020)
This paper investigates the effects of the Brexit announcement on the British economy. For this, we use a counterfactual analysis methodology, predicting a set of macroeconomic variables of the British economy in a scenario where the Brexit announcement did not happen and measuring what drifted away from its effective value. To forecast the variables we use the ARIMA method. Our conclusions are that if Brexit had not been announced: i) the exchange rate of the Pound Sterling against the US Dollar would not have had such a sharp depreciation trend; ii) real wage growth would not have been as high after the referendum; iii) the growth rate of the consumer price index would not have had such a strong growth trend and iv) the Gross Domestic Product would have grown at a higher pace and after three years of Brexit announcement it would have been 3% higher.